Peer effects on low-income children's learning and development. (December 2018) - Choi, Ji Young; Castle, Sherri; Burchinal, Margaret; Horm, Diane; Guss, Shannon; Bingham, Gary E.
Abstract: Using data from a large study of 78 high-quality Head Start classrooms in 12 sites across the U.S., this study examined whether peers' receptive vocabulary skills and teacher-reported social-emotional (S-E) functioning (i.e., behavior problems and self-regulation) measured at the beginning of the preschool year were related to children's gains in these three domains over a school year. Analyses included over 75% of the children in each classroom and produced three noteworthy findings. First, children in classrooms where average peers had higher behavior problems demonstrated increased teacher-reported behavior problems themselves at the end of the year. Second, children in classrooms where average peers had higher self-regulation skills demonstrated larger gains in teacher-reported self-regulation skills at the end of the school year. Third, peers' higher baseline self-regulation skills were found to be associated with children's higher self-regulation in spring, especially when children began the school year with higher levels of self-regulation. This finding indicates that children who have higher baseline self-regulation may be better positioned to benefit from their peers' high self-regulation in developing their own self-regulation skills. In contrast, no evidence was found that peers' baseline receptive vocabulary skills were related to children's receptive vocabulary gains over a school year. Additionally, no significant cross-domain peer effects were found between peers' baseline S-E functioning and children's receptive vocabulary gains nor peers' baseline receptive vocabulary skills and children's S-E development over a school year. Implications of these findings for classroom practice and further research are discussed.